Structural Information and Communication Complexity 21st International Colloquium, SIROCCO 2014, Takayama, Japan, July 23-25, 2014, Proceedings - Halldórsson, Magnús M. (Theoretical Computer Science and General Issues, 2014)
This book constitutes the refereed proceedings of the 21st International Colloquium on Structural Information and Communication Complexity, SIROCCO 2014, held in Takayama, Japan, in July 2014. The 24  full papers presented  together with 5 invited talks were carefully reviewed and selected from 51 submissions. The focus of the colloquium is on following subjects Shared Memory, and Multiparty Communication, Network Optimization, CONGEST Algorithms and Lower Bounds, Wireless networks, Aggregation and Creation Games in Networks, Patrolling and Barrier Coverage, Exploration, Rendevous, and Mobile Agents.